1997
DOI: 10.1200/jco.1997.15.3.1261
|View full text |Cite
|
Sign up to set email alerts
|

Does a centralized radiotherapy system provide adequate access to care?

Abstract: The low and uneven rates of radiotherapy use across the province indicate that Ontario's centralized radiotherapy system does not, at present, provide adequate or equitable access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 11 publications
3
54
0
Order By: Relevance
“…Between January 1995 and January 2015, the number of cancer centres providing rt in Canada more than doubled, improving geographic access to rt. Building additional rt centres was motivated in part by long wait times for rt, and evidence that rt utilization declined with distance to the cancer centre and improved when access was more convenient 3,6,7,[11][12][13][14][15] . Improving geographic access by building cancer centres is one way to be patientcentred, because more convenient locations respond to a patient preference to access care closer to home.…”
Section: Figurementioning
confidence: 99%
“…Between January 1995 and January 2015, the number of cancer centres providing rt in Canada more than doubled, improving geographic access to rt. Building additional rt centres was motivated in part by long wait times for rt, and evidence that rt utilization declined with distance to the cancer centre and improved when access was more convenient 3,6,7,[11][12][13][14][15] . Improving geographic access by building cancer centres is one way to be patientcentred, because more convenient locations respond to a patient preference to access care closer to home.…”
Section: Figurementioning
confidence: 99%
“…Like these there are other studies which show better outcomes and cost-effectiveness for RT treatments for different types of cancer and their stages. However, measured access to RT services has established that utilization rates are well below this optimal number (Mackillop et al, 1997;Barton 2000;Einhorn et al 1996;Athas et al, 2000) clearly demonstrating the existence of barriers to access existing RT services.…”
Section: Introductionmentioning
confidence: 99%
“…Since the proximity of RT facilities to home has been identified as a major factor enhancing accessibility to and utilization of RT services (Mackillop et al, 1997;, it is likely that remote and rural patients are facing limited accessibility to radiotherapy on the basis of inadequate transportation and lengthy travel. A literature review has highlighted travel as a perceived barrier to cancer treatment (Payne et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have also suggested that, in addition to a negative emotional and psychological impact, oop costs may influence care-related decisions made by patients [6][7][8][9][10][11][12][13][14] . For example, researchers in Canada have suggested that high oop costs may have discouraged rural, low-income, and insurancedeprived patients from pursuing certain forms of treatment such as breast-conserving surgery [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, researchers in Canada have suggested that high oop costs may have discouraged rural, low-income, and insurancedeprived patients from pursuing certain forms of treatment such as breast-conserving surgery [10][11][12][13][14] . Using qualitative interviews with cancer care providers, researchers in Newfoundland and Labrador (hereinafter Newfoundland) suggested that patients may adopt care-compromising strategies (such as…”
Section: Introductionmentioning
confidence: 99%